Implementasi Pembelajaran Akidah Akhlak Model Problem Based Learning dalam Meningkatkan Kompetensi Sikap Spiritual Peserta Didik di MTS YPM 2 Sidoarjo - Ilma, Liulil Ussisa; Imama , Imama; Zuhri , Badrudin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The problems addressed in this study are: How is the implementation of Akidah Akhlak learning using the Problem Based Learning model in improving students’ spiritual attitude competence at MTs YPM 2 Sidoarjo? What is the role of teachers and students in Akidah Akhlak learning using the Problem Based Learning model at MTs YPM 2 Sidoarjo? What are the supporting and inhibiting factors in the implementation of Akidah Akhlak learning using the Problem Based Learning model in enhancing students’ spiritual attitude competence at MTs YPM 2 Sidoarjo?.The objectives of this study are to identify the implementation of Akidah Akhlak learning using the Problem Based Learning model in improving students’ spiritual attitude competence at MTs YPM 2 Sidoarjo; to determine the roles of teachers and students in Akidah Akhlak learning using the Problem Based Learning model at MTs YPM 2 Sidoarjo; and to identify the supporting and inhibiting factors in the implementation of the Problem Based Learning model in enhancing students’ spiritual attitude competence at MTs YPM 2 Sidoarjo. Based on the type of research, the researcher employed a qualitative approach. Through this approach, the study produces descriptive data, as it aims to describe conditions or phenomena as they naturally occur. To obtain the necessary data, the researcher used observation, interviews, and documentation as the data collection techniques. Meanwhile, the data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results of the study show that this learning model is highly effective and efficient. In the learning process, students are active, creative, and able to express their opinions, which makes the classroom atmosphere more dynamic. This occurs because the teacher acts as a facilitator while students serve as the main subjects. Through this learning process, students are encouraged to learn about phenomena or events in their surrounding environment and daily life, which ultimately enhances their spiritual attitude competence. Supporting factors of the Problem Based Learning model include adequate facilities and infrastructure that support the learning process, competent teachers with broad insight, and the availability of learning materials relevant to the topic. The inhibiting factors include a lack of learning motivation among students, some students feeling sleepy, lacking concentration, and experiencing fatigue, as well as negative peer influence. Permasalahan dalam penelitian ini adalah, Bagaiamana Implementasi Pembelajaran Akidah Akhlak Model Problem Based Learning dalam Meningkatkan Kompetensi Sikap Spiritual Peserta Didik di MTs YPM 2 Sidoarjo? Bagaimana peran Guru dan Peserta didik dalam pembelajaran Akidah Akhlak Model Problem Based Learning di MTs YPM 2 Sidoarjo? Apa saja faktor pendukung dan faktor penghambat implementasi pembelajaran Akidah Akhlak Model Problem Based Learning dalam meningkatkan Kompetensi Sikap Spiritual Peserta Didik di MTs YPM 2 Sidoarjo?.Tujuan penelitian ini untuk Mengetahui Implementasi Pembelajaran Akidah Akhlak Model Problem Based Learning dalam Meningkatkan Kompetensi Sikap Spiritual Peserta Didik di MTs YPM 2 Sidoarjo. Mengetahui peran Guru dan Peserta Didik dalam Pembelajaran Akidah Akhlak Model Problem Based Learning di MTs YPM 2 Sidoarjo. Mengetahui apa saja faktor pendukung dan faktor penghambat implementasi pembelajaran Akidah Akhlak Model Problem Based Learning dalam meningkatkan kompetensi sikap spiritual peserta didik di Mts YPM 2 Sidoarjo. Dilihat dari jenis penelitian, peneliti menggunakan pendekatan kualitatif. Dengan menggunakan pendekatan ini, maka peneliti akan menghasilkan data deskriptif dimana penelitian ini bertujuan untuk mendeskripsikan suatu keadaan atau fenomena-fenomena secara apa adanya. Untuk mendapatkan data yang diperlukan peneliti menggunakan teknik pengumpulan data observasi, wawancara dan dokumentasi. Sedangkan untuk analisis datanya menggunakan reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pada model pembelajaran ini sangat efektif dan efisien. Dilihat dari proses pembelajaran peserta didik ikut aktif, kreatif dan mampu mengungkapkan pendapatnya sehingga suasana kelas menjadi lebih hidup. Karena gurur berperan sebagai fasilitator dan peserta didik sebagai subjek. Dari pembelajaran tersebut maka akan mendorong peserta didik dapat mempelajari suatu fenomena atau kejadian yang berada dilingkungan sekitar dalam kehidupan sehari-hari serta dapat meningkatkan kompetensi sikap spiritual. Adapun faktor-faktor yang mendukung model Problem Based Learning adalah Sarana prasarana yang memadai untuk mempermudah pembelajaran, Guru yang berkompeten dan berwawasan luas, Tersedianya bahan ajar sesuai dengan materi yang dipelajari. Adapun faktor penghambat dari model Problem Based Learning antara lain: Kurangnya minat belajar peserta didik, Beberapa peserta didik mengantuk, kurang konsentrasi, dan kecapekan, Pengaruh dari teman yang kurang baik.